Beyond individual-level factors that influence family planning uptake among women with diabetes mellitus: a systematic literature review - Idayu Badilla Idris; Sarah Awang Dahlan; Rahana Abd Rahman; Azmawati Mohammed Nawi (BMC Public Health)
Abstract Background The prevalence of diabetes mellitus among women increased consistently together with the increase in the overall prevalence of diabetes mellitus globally. One of the components in holistic diabetes care among women are preconception interventions. Family planning usage has been one of the components in preconception care among this group of population, especially among women with unoptimised diabetes mellitus, where family planning may allow disease optimisation prior to pregnancy. This systematic review thus aimed to synthesise evidences and improve understanding on the non-individual factors in influencing family planning practice among women with diabetes mellitus. Methods PubMed, Web of Science and EBSCOHost was systematically searched for empirical studies between 2000 and 2023 that discussed on factors that influenced family planning usage among women with diabetes. This systematic literature review was conducted in accordance to Joanna Briggs Institute’s approach for conducting systematic review of associations. Factors were categorised to either individual and non-individual factors. Narrative synthesis approach was adopted that appropriately accommodates the heterogeneity of the reviewed studies. Results A total of 29 studies met the inclusion criteria. Studies included in this review mostly reported individual-level factors that influence family planning practice among women with diabetes mellitus which were mainly the presence of diseases and other sociodemographic characteristics. Only six studies reported factors beyond individual variables which include geographic region, access to care, opinion of significant others, healthcare providers’ perception, role of doctors and types of service providers. Conclusions This systematic review provides evidences that highlighted the gap in knowledge on variables that were beyond individual-level factors which influence family planning practice among women with diabetes mellitus. Further studies that explored structural and systemic factors may benefit future program planning to identify and target modifiable factors.